Health promoting university programs as a strategy for reducing tuberculosis stigma and enhancing environmental - Ahmadi, Arbi; Idris, Irma; Tahrim, Nurmutmainna; Nisa, Nur Aulia; Alifah, Nahda Fatin (Asian Journal of Toxicology, Environmental, and Occupational Health, 2025)
Introduction: Tuberculosis (TB or TBC) is a deadly infectious disease that surpasses HIV and malaria as the leading cause of infectious death. Indonesia ranks second in global TB cases. The main challenges in eliminating TB are stigma, social problems and low adherence to treatment due to access to services. The Health Promoting University aims to increase health awareness in universities. This study encourages the participation of the younger generation to voice TB issues in their surroundings and on social media. Method: This research uses a descriptive qualitative method, analyzing secondary data from regulations and literature and a mini survey to measure Indonesian students' understanding of Tuberculosis. Findings: The results of the research show that Indonesia has the second highest TB cases in the world, with vulnerable groups such as students exposed through droplets when sufferers cough or sneeze. Risk factors for students include fatigue from studying, smoking habits, and intense social interactions. WHO data shows that the TB death rate in Indonesia will reach 134,000 in 2022. TB also triggers stigma and discrimination, hindering patients in education and employment. Increasing awareness supported by concrete policies is the main solution in overcoming the spread of TB. Conclusion: Universities in Indonesia have a strategic role in creating a healthy campus environment, in accordance with Law No. 12 of 2012 concerning Higher Education and Regulation of the Minister of Education and Culture No. 3 of 2020. Through the Health Promoting University, universities are expected to integrate health education, such as TB prevention, into campus culture. Novelty/Originality of this article: This program involves various efforts, such as the formation of TB prevention communities, socialization of clean living behavior, routine health checks, and a "Zero Tolerance" policy for health risks. With this approach, campuses contribute to national efforts to eradicate TB, create a healthy learning environment, and increase students' health awareness.